Predicting the Perception of SMEs on the Selection of Bank Decision in Pakistan: A Partial Least Square (PLS) Model - Zafar Iqbal; Dr. Saima Batool; Dr. Muhammad Khalique; Dr. Mushtaq A. Sajid (Journal of Business & Tourism, 2021)
The main objective of this study was to examine the main factors which may have influence on the bank selection decision in Pakistan. Quality of service, quality of service provider, interaction dimensions and relationship image recommendations experience were employed as independent variables while the bank selection decision SMEs was used as a dependent variable. The data were gathered through structured questionnaire survey. A total of 300 questionnaires were distributed to the targeted respondents while 223 were involved in the study. The respondents were selected through purposive sampling technique. Four research hypotheses were established. Smart Partial Least Square (PLS) 3 was used to test the proposed research hypotheses. The empirical findings of this study showed that the four research hypotheses were supported. This is the first study in Pakistan to address this issue.